2004
DOI: 10.1023/b:bmmd.0000042048.18186.ff
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Immunological Properties of Cytokines Conjugated to Dendritic Polymers

Abstract: Here we describe a post-translational modification of SC-63032, a variant of the species restricted, multi-lineage hematopoeitic factor human interleukin-3 (hIL-3). We have made two new dendritic polymer (polyamidoamine or PAMAM dendrimers, generation 5)-SC-63032 bioconjugates. Using two distinct chemistries (one of which is novel to this work), we achieved site-specific conjugation with respect to the amino acid in the proteins ligated to the dendrimers. In both bioconjugates, conjugated cytokine maintains it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…chemical warfare agents, and biological species [1]- [4]. They are used mostly to detect the adsorption or attachment of protein molecules [5], cells [6], bacteria [7], or the immunological properties of cytokines conjugated to organisms on the plate surface of two-port IDTs [8].…”
Section: Introductionmentioning
confidence: 99%
“…chemical warfare agents, and biological species [1]- [4]. They are used mostly to detect the adsorption or attachment of protein molecules [5], cells [6], bacteria [7], or the immunological properties of cytokines conjugated to organisms on the plate surface of two-port IDTs [8].…”
Section: Introductionmentioning
confidence: 99%
“…This collection is based on a unique set of dendritic structural parameters-cyclo(triphosphazene) core, benzylhydrazone branches and phosphonic acid surface-and was designed to study the influence of phosphonate (phosphonic acid) surface loading towards the activation of human monocytes ex vivo. Starting from the versatile hexachloro-cyclo(triphosphazene) N 3 P 3 Cl 6 , six first-generation dendrimers were obtained, bearing one to six full branches, that lead to 4,8,12,16,20 and 24 phosphonate termini, respectively. The surface loading was also explored at the limit of dense packing by means of a first-generation dendrimer having a cyclo(tetraphosphazene) core and bearing 32 termini, and with a first-generation dendrimer based on a AB 2 /CD 5 growing pattern and bearing 60 termini.…”
mentioning
confidence: 99%
“…The in vitro immunostimulating properties of this conjugate were reported to be lower than those of free hIL-3. [20] However, we have recently shown that phosphorus-containing dendrimers [21] decorated with suitable amino-bismethylene phosphonic acid derivatives on the surface were able to both promote the amplification of fully functional NK cells [22] and to provide the activation of monocytes from healthy human peripheral blood mononuclear cells (PBMC) in culture, [23] whereas the corresponding surface monomers were unable to provide such activities. Monocytes are a pivotal subpopulation of the innate immune system.…”
mentioning
confidence: 99%
“…In the past, natural proteins have commonly been used as carriers to generate antibodies to small molecules; now an alternative strategy using dendrimers has been demonstrated. In particular, unmodified PAMAM dendrimers that fail to elicit an antibody response on their own become haptenized upon protein conjugation and generate a dendrimer-dependent antigenic response [86,87]. A specific example of this technique is provided by the dendrimeric presentation of antigenic HIV peptides, which proved superior to other multimeric presentation strategies, such as conjugation to dextran [88].…”
Section: Dendrimer Conjugates Can Be Used As Vaccinesmentioning
confidence: 99%